Modern human origins - Klein, Richard (Henry Stewart Talks, 2007)
Human evolution, Anatomical differences between Neanderthals and modern humans, African origin of modern human anatomy, Subsequent African origin of modern human behavior, including art and jewellery, Fate of the Neanderthals and other non-modern humans, Possibility that a genetic change prompted the modern human expansion from Africa